The Education to Health Community and Legal Impacts for Health Protocol Violers of Covid-19 In Indonesia - Sri Setiawati (International Journal of Law Society Services, 2022)
This reasearch purposes to socialize the impact of violating health protocols during the COVID-19 pandemic in Indonesia. The implementation of the Health Protocol in dealing with the spread of the COVID-19 virus in Indonesia is a crucial thing to be socialized. Violations of health protocols have legal consequences and the quality of public health. The Head of Wonoplumbon Sub-district, Mijen Sub-district, hopes that there will be socialization of the legal consequences and quality of public health for violating health protocols. The method used in this activity is the Participatory Learning Methods method. The result of this activity is that violations of health protocols can have the impact of increasing the number of patients exposed and dying, as well as high hospital occupancy, resulting in an increase in the number of health workers who are also exposed and die. Violators of health protocols, especially social distancing, can be subject to criminal sanctions in accordance with applicable laws.